Alcoolismo e Strongyloides stercoralis : investigação de possíveis fatores associados à maior prevalência do nematoide em alcoolistas crônicos - Ribeiro, Steveen Rios (2017)
Introduction. Strongyloides stercoralis (Bavay, 1876) is an intestinal nematode that can proliferate in the host by autoinfection, and persist for decades without further exposure to exogenous infection. The prevalence of the parasite is poorly known in the state. Higher prevalence of S. stercoralis in chronic alcoholic patients than in non-alcoholics, attended at the same hospital, has been reported, but there are doubts about if there is a greater exposure to the parasite or greater survival and fecundity of females in the duodenum would increase the chance of encountering larvae in the feces. Objectives. To evaluate: (a) the prevalence of S. stercoralis in the state on samples of schoolchildren aged 7 to 14 years and samples from patients attended at the different outpatient clinics of the Hospital C.A. Moraes (HUCAM) and Hospital Concórdia at Sta. Maria de Jetibá; (b) the prevalence of the parasite on samples of alcoholics and non-alcoholics in the Department of Gastroenterology of HUCAM and Hospital Concordia; (c) the number of S. stercoralis rabditoid larvae on stools of alcoholics and non-alcoholics patients; (d) the anti-S. stercoralis antibodies on serum and Treg lymphocytes (Treg) in peripheral blood in alcoholics and non-alcoholics; (e) the use of the conventional PCR method on stool samples of alcoholic and non-alcoholic patients, to confirm the difference in prevalence observed between the two groups.